IMPLEMENTASI KREDIT TANPA AGUNAN DALAM HAL DEBITUR WANPRESTASI PADA PT BANK OVERSEAS CHINEESE BANKING CORPORATION (OCBC) NISP TBK CABANG DENPASAR - Agus Sukyantara, I Putu; Puspawati, I Gusti Ayu; Purwanti, Ni Putu (Kertha Semaya : Journal Ilmu Hukum, 2013)
Studied empirically in the banking institutions give priority to the mortgage loans not only in the form of a moving object or objects do not move, but the bank can also provide loans without collateral on the basis of belief in providing bank credit to provide loans without collateral on the basis of trust. Collateral of the debtor only an additional guarantee submitted by the debtor to the creditor.. However, the collateral of the debtor only an additional guarantee submitted by the debtor to the creditor. This is to convince the creditor if the debtor can not perform its obligations in the future and rescue efforts unsecured loans can be made through alternative handling rescheduling, return requirements and restructuring.
Keywords: Banking, Credit, Debtor, Wanprestasi